The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27144591
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Terpenoid Biosynthesis Genes in Euphorbia maculata via Full-Length cDNA Sequencing

Abstract: The annual herb Euphorbia maculata L. produces anti-inflammatory and biologically active substances such as triterpenoids, tannins, and polyphenols, and it is used in traditional Chinese medicine. Of these bioactive compounds, terpenoids, also called isoprenoids, are major secondary metabolites in E. maculata. Full-length cDNA sequencing was carried out to characterize the transcripts of terpenoid biosynthesis reference genes and determine the copy numbers of their isoforms using PacBio SMRT sequencing technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The most abundant compounds in the natural products in general are terpenoids (Yang et al, 2020), however, the study findings reported low levels in terpenoids while a moderate level was reported by Njeru and Meshack (2016). Previous studies on differential gene expression analysis revealed that the expression level differed among gene paralogs involved in terpenoid biosynthesis in the leaf, stem, and root of other related plants (Jeon et al, 2022). Plants' terpenoids are anti-hyperglycemic, antiinflammatory, anti-parasitic, anti-viral, anti-cancer, antimicrobial and they render skin permissible to many drugs across cell membrane (Ramawat and Mérillon, 2013).…”
Section: Plant Extraction and Phytochemical Screeningmentioning
confidence: 56%
“…The most abundant compounds in the natural products in general are terpenoids (Yang et al, 2020), however, the study findings reported low levels in terpenoids while a moderate level was reported by Njeru and Meshack (2016). Previous studies on differential gene expression analysis revealed that the expression level differed among gene paralogs involved in terpenoid biosynthesis in the leaf, stem, and root of other related plants (Jeon et al, 2022). Plants' terpenoids are anti-hyperglycemic, antiinflammatory, anti-parasitic, anti-viral, anti-cancer, antimicrobial and they render skin permissible to many drugs across cell membrane (Ramawat and Mérillon, 2013).…”
Section: Plant Extraction and Phytochemical Screeningmentioning
confidence: 56%